Activities for teaching statistics and research methods a guide for psychology instructors - Stowell, Jeffrey R.; Addison, William E. (Washington, DC American Psychological Association, 2017)
Statistics and research methods are core components of both advanced placement and undergraduate psychology curricula. Yet, these courses are often challenging for many students. This book offers original, pedagogically sound, classroom-tested activities that engage students, teach principles, and inspire teachers. Each chapter contains classroom exercises that are practical and easily implemented, and help students learn core principles in ways that are fun and engaging.
I. Statistics -- 1. Reducing anxiety in the statistics classroom -- 2. How to lie with the Y-Axis -- 3. Summarizing data using measures of central tendency: a group activity -- 4. How fast is your internet? An activity for teaching variance and standard deviation -- 5. Getting dicey: thinking about normal distributions and descriptive statistics -- 6. A low-anxiety introduction to the standard normal distribution and measures of relative standing -- 7. Using the heat hypothesis to explore the statistical methods of correlation and regression -- 8. Active learning for understanding sampling distributions -- 9. Testin students for ESP: Demonstrating the role of probability in hypothesis testing -- 10. Using a TV game show format to demonstrate confidence intervals -- 11. Real-life application of type I and type II decision errors -- 12. Factors that influence statistical power -- 13. An interdisciplinary activity for p Values, effect sizes, and the Law of small numbers -- II. Research methods -- 14. An activity for teaching the scientific method -- 15. Linking identification of independent and dependent Variables to the goals of science -- 16. Everything is awesome: building operational Definitions with play-Doh and LEGOs -- 17. A demonstration of random assignment that is guaranteed to work (95% of the Time) -- 18. Identifying confounding factors in psychology research -- 19. Demonstrating experimenter and participant bias -- 20. The most unethical researcher: an activity for demonstrating research ethics in psychology -- 21. The ethics of behavioral research using animals: A classroom exercise -- 22. Demonstrating interobserver reliability in naturalistic settings -- 23. Using a classic model of stress to teach survey construction and analysis.
Includes bibliographical references and index.
Keywords: Psychology -- Statistical methods; Psychology -- Methodology; Psychology -- Study and teaching